Food Warmer System Based on DHT-22 - Asti Riani Putri; Putri Nur Rahayu (JAREE (Journal on Advanced Research in Electrical Engineering), 2020)
A warm meal will make those who eat it feel comfortable, especially those who have a history of suffering from gastritis or respiratory problems such as asthma from the incident means that they need a portable food warmer that can warm food wherever and whenever. So the purpose of this research is to create a temperature control and monitoring system automatically using a DHT22 sensor as a temperature gauge and fan, and incandescent lamps as a stabilizer of its temperature. The method used in the temperature regulation system using fuzzy logic. Fuzzy logic is a method of control system that can provide decisions that resemble humans. By determining the membership and fuzzy logic rules in the microcontroller as the brain, the temperature can be adjusted automatically. The result is making a food warmer that can maintain heat stability from food and can be taken anywhere. Keywords: DHT-22, fuzzy logic, temperature.